2016
DOI: 10.1016/j.chest.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

SERVE-HF: More Questions Than Answers

Abstract: The recent online publication of the SERVE-HF trial that evaluated the effect of treating central sleep apnea (CSA) with an adaptive servoventilation (ASV) device in patients with heart failure and reduced ejection fraction (HFrEF) has raised serious concerns about the safety of ASV in these patients. Not only was ASV ineffective but post hoc analysis found excess cardiovascular mortality in treated patients. The authors cited as one explanation an unfounded notion that CSA is a compensatory mechanism with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 26 publications
1
44
0
6
Order By: Relevance
“…In the context of the SERVE‐HF study,23 a trial that has raised serious concerns about the effect of adaptative servoventilation in patients with HFrEF and CSA, physicians are waiting for new trials and alternative therapies. Because of its reported beneficial effects and its mechanism of action, we believe that sacubitril–valsartan needs to be evaluated 25.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the SERVE‐HF study,23 a trial that has raised serious concerns about the effect of adaptative servoventilation in patients with HFrEF and CSA, physicians are waiting for new trials and alternative therapies. Because of its reported beneficial effects and its mechanism of action, we believe that sacubitril–valsartan needs to be evaluated 25.…”
Section: Discussionmentioning
confidence: 99%
“…74- 80 It was noted that a number of individuals with HFpEF slipped into this trial. In the majority of trial participants it was home polygraphy that was used to diagnose CSA.…”
Section: Advent-hf: a Pivotal Hf Trialmentioning
confidence: 99%
“…The predominant use of a full face rather than a nasal mask may have compromised adherence, which was, on average, only 3.7 h/night and also encouraged CO2 rebreathing. 80 A second hypothesis is that by inducing hyperventilation the mv-ASV algorithm might have created an enhanced metabolic substrate for ventricular arrhythmias.…”
Section: Serve-hf the Treatment Of Sleep-disordered Breathing With Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson and Johnson to "Updated Adaptive Servo-Ventilation (ASV) Recommendations for the 2012 AASM Guideline." 1 The concerns that they raise, along with other commentaries 2,3 in response to Cowie et al 4 are reminiscent of the controversy following the publication of the CanPAP study in 2005. 5 The SERVE-HF study was a large randomized controlled trial utilizing intention to treat analysis which found that ASV had no impact on the primary endpoints (the first event of lifesaving cardiovascular intervention, unplanned hospitalization for worsening heart failure, or death from any cause).…”
mentioning
confidence: 99%